Peran kursus politik P.S.I.I Bandung dalam meningkatkan kesadaran politik tahun 1931 - Mutiara Indah Prameswari (Priangan: Journal of Islamic Sundanese Culture, 2025)
The purpose of writing this article is to study the political course of the Sarekat Islam Party (PSII) in Bandung. Sarekat Islam is a party known for having the largest number of members during the leadership of HOS Tjokroaminoto. The research method used is historical research, specifically literature study, by comparing and combining the data and sources found. In 1920, there was turmoil among parties to win the hearts of the people through various means, from verbal persuasion to physical actions, which resulted in public fear. Therefore, PSII Bandung took the initiative to establish a party course institution to attract the public's interest and retain its members.